2021
DOI: 10.1097/jsa.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Meniscus Injury

Abstract: Meniscus surgery is one of the most commonly performed orthopedic procedures worldwide. Modifiable risk factors for meniscus injury include body mass index, participation in athletics and occupation. Nonmodifiable risk factors include age, sex, lower extremity alignment, discoid meniscus, ligamentous laxity, and biconcave tibial plateau. Conditions commonly associated with meniscal injury are osteoarthritis, anterior cruciate ligament injury, and tibial plateau fractures. Tear type and location vary by patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 91 publications
(281 reference statements)
0
49
0
11
Order By: Relevance
“…The quantification of protein biomarkers, as a means of detecting specific types of meniscal injuries, has more recently become an area of active investigation with the popularization of sophisticated multiplexing technologies such as Luminex, which allow nanoscale detection of robust sets of soluble protein markers. A meniscus injury is linked to the development of PTOA ( Kennedy et al, 2020 ; Sherman et al, 2020 ; Tarafder et al, 2020 ; Adams et al, 2021 ). As such, the events that occur after traumatic injury or degenerative changes in the meniscus that govern the progression of OA are regulated at the molecular level.…”
Section: Gauging the Success Of Emerging Meniscus Repair Strategies In The Pre-clinical Stagementioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of protein biomarkers, as a means of detecting specific types of meniscal injuries, has more recently become an area of active investigation with the popularization of sophisticated multiplexing technologies such as Luminex, which allow nanoscale detection of robust sets of soluble protein markers. A meniscus injury is linked to the development of PTOA ( Kennedy et al, 2020 ; Sherman et al, 2020 ; Tarafder et al, 2020 ; Adams et al, 2021 ). As such, the events that occur after traumatic injury or degenerative changes in the meniscus that govern the progression of OA are regulated at the molecular level.…”
Section: Gauging the Success Of Emerging Meniscus Repair Strategies In The Pre-clinical Stagementioning
confidence: 99%
“…Initially, the meniscus was considered to be vestigial tissue, which can simply be removed surgically upon major injury, as a means of alleviating pain and restoring function to the knee joint ( Chivers and Howitt, 2009 ; McNulty and Guilak, 2015 ). However, it is now known that the absence of, or injury to, meniscal tissue significantly increases the risk of post-traumatic osteoarthritis (PTOA) ( Badlani et al, 2013 ; Chang and Brophy, 2020 ; Rai et al, 2020 ; Adams et al, 2021 ; Bedrin et al, 2021 ). Indeed, according to a recent 2020 epidemiological study of young adults, approximately 13% of patients with meniscus injuries develop OA by 18 years post-injury, whereas only about 3% of patients with uninjured knees developed the disease ( Snoeker et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the learning that takes place with EMG-BF not only makes it easier to acquire greater awareness of the activity of the muscle, but also improves its involuntary activity [9,14]. This is of the greatest significance because it makes it possible to improve the outlook for future injuries, in a context such as soccer in which knee injuries are very common [22,23,33,37].…”
Section: Discussionmentioning
confidence: 99%
“…One of the classic scenarios that can emerge while playing soccer is a meniscal lesion [32][33][34], which may present with varying degrees of severity depending on the damage caused to its structure and whether it occurs in the medial or the lateral meniscus [35]. There is often a substantial alteration in the structure of the meniscus requiring surgical intervention, and it is one of the most common traumatological procedures in the general population [36], specifically in soccer [33,37].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors are risk factors for meniscal tears, increasing the likelihood of developing meniscal tears. The non-modifiable risk factors for meniscal tears include sex, where the incidence in men is 2.5 times more than in women [ 11 ]. Meniscal tears are more in individuals with a biconcave tibial plateau, a discoid meniscus, those with lower extremity alignment, and those with ligamentous laxity.…”
Section: Reviewmentioning
confidence: 99%